The oriental obsession: Islamic inspiration in British and American art and architecture 1500 - 1920 - Sweetman, John (Cambridge studies in the history of art, 1988)
John Sweetman: "The Oriental Obsession". Islamic Inspiration in British and American Art and Architecture 1500-1920. Cambridge University Press, Cambridge 1988. 327 S., 160 Abb., 37,50 engl. Pfund